Self-actualization of The Main Character Hujan Novel by Tere Liye A Review of Psychology Abraham Maslow - Chintya Bayu Lestari; Siti Gomo Attas (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
AbstrackThis research aims to self-actualization of depictions of the main characters of the Novel Hujan work of Tere Liye and structure of which is contained in the novel. This research is qualitative research using the method of content analysis. The approach used ini this study is the structural approach and psychology Abraham Maslow. In this study, there are four ways of engineering data collection performed by the researchers, namely: (a) read and understand the contents of the novel’s story in depth. (b) the identification of each of the novel’s structure, namely: tokoh, characters, setting, and theme. (c) conduct a classification with classified the quotations form phrases, clauses, sentences, or paragraphs containing the existence of self-actualization character and basic necessities to achieve self-actualization. (d) hold a study library to get secondary data as supplementary data about self-actulization of the main character. In qualitative researches apply as key research instruments. The results of this study indicate that there are six basic needs based on Maslow’s hierarchy. Six basic needs are contained in the main character of the novel Hujan by Tere Liye. The main character can actualize himself although only a few basic needs that have been fulfilled in the character, meaning that six basic needs are not all owened by characters. Although they only meet some of the needs of the six basic needs, they can actualize themselves.Keywords: self-actualization, the Novel, the main charcter, and the psychology of Abraham Maslow